Pyk2 mediates increased adrenergic contractile responses in arteries from DOCA-salt mice — Vasoactive Peptide Symposium - Giachini, Fernanda R.C., Msc; Carneiro, Fernando S., Msc; Lima, Victor V; Carneiro, Zidonia N; Carvalho, Maria Helena C., PhD; Fortes, Zuleica B., PhD; Webb, R. Clinton, PhD; Tostes, Rita C., PhD (Journal of the American Society of Hypertension, 2008)
Abstract The calcium-dependent proline-rich tyrosine kinase (Pyk2), a nonreceptor protein activated by tyrosine phosphorylation, links G protein-coupled receptors to vascular responses. We tested the hypothesis that enhanced vascular reactivity in deoxycorticosterone acetate (DOCA)-salt hypertensive mice is due to increased activation of Pyk2. Aorta and small mesenteric arteries from DOCA-salt and uninephrectomized (UNI) male C57Bl/6 mice were used. Systolic blood pressure (mm Hg) was higher in DOCA (126 ± 3) vs. UNI (100 ± 4) mice. Vascular responses to phenylephrine (1 nM to 100 μM) were greater both in aorta and small mesenteric arteries from DOCA-salt than UNI, but treatment with Tyrphostin A-9 (0.1 μM, Pyk2 inhibitor) abolished the difference among the groups. Pyk2 levels, as well as phospho-Pyk2Tyr402 , paxillin, and phospho-paxillinTyr118 were increased in DOCA-salt aorta. Incubation of vessels with Tyrphostin A-9 restored phosphorylation of Pyk2 and paxillin. Increased activation of Pyk2 contributes to increased vascular contractile responses in DOCA-salt mice.